Development of Nano Textured Solar PV Cell for Photovoltaic and Self Cleaning Applications Using Different Coating Technique - Natarajan Purushothaman, R Elansezhian, A V Raviprakash (International Journal of Advanced Science and Technology, 2020)
Renewable sources of energy are most researched fields in recent times due to rapid decline in availability of fossil fuels. Recent research is aimed to improve the output of solar cells in terms of electrical efficiency. This has been achieved through several methods out of which alteration of physical, electrical and optical properties of solar cells is found to be a novel strategy in recent times with the advent of nano-technology coupled with deposition techniques. In this research, a two different coating techniques were carried to improve an optical properties, self-cleaning and performance of the solar PV cells. Here Cu, Ag, Al was deposited over the Pv cell for metallization purpose by using RF and DC magnetron sputtering process and nano structured titanium dioxide were synthesized by using sol-gel dip coating method to coated over the glass substrate and placed over the coated solar Pv cells. During sputtering process, the process parameters such as power, deposition time and substrate temperature were optimized and corresponding coating thickness, optical properties and surface topography were investigated. The surface properties was enhanced when the power increased from 15W to 45W. The maximum surface roughness of 6nm were reached at the power of 45W with the deposition rate of 5-7 mins. The surface morphology and topography was characterized by using SEM and AFM which shows uniform coating with spherical shaped nanoparticles deposited over substrate surface at 3000C. The optical properties such as absorption and reflection were investigated by using UV-VIS spectrometer which indicates that the absorption was increased from 1.2% to 1.5% at the wavelength range from 250 to 314nm and the reflectance was reduced from 23% to 5.7% after the TiO2 deposition and the performance of solar Pv cell was increased from 14.22% to 17.54%. The complete experimental details, results and analysis are reported in this paper.